1994
DOI: 10.1046/j.1471-4159.1994.63062217.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ca2+/Calmodulin‐Dependent Protein Kinase II Following Ischemia: A Comparison Between CA1 and Dentate Gyrus in a Hippocampal Slice Model

Abstract: TX 77225, U .S .A . Abbreviations used: CaM-KII, Ca Z+ /calmodulin-dependent protein kinase 11 ; EPSP, excitatory postsynaptic potential ; MAP2, microtubule-associated protein 2 ; NMDA, N-methyl-D-aspartate ; PKA, cyclic AMP-dependent protein kinase ; PKC, protein kinase C ; PKI, peptide inhibitor of PKA .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…CamKII protein and activity levels are decreased after episodes of cerebral ischemia (Churn et al, 1990;Onodera et al, 1990;Morioka et al, 1992;Yamamoto et al, 1992). These alterations are more persistent in regions that are selectively vulnerable to ischemic cell death (Westgate et al, 1994;Hu and Wieloch, 1995). Also, decreases in CamKII occur after the onset of seizure activity in a variety of animal models (Goldenring et al, 1986;Murray et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…CamKII protein and activity levels are decreased after episodes of cerebral ischemia (Churn et al, 1990;Onodera et al, 1990;Morioka et al, 1992;Yamamoto et al, 1992). These alterations are more persistent in regions that are selectively vulnerable to ischemic cell death (Westgate et al, 1994;Hu and Wieloch, 1995). Also, decreases in CamKII occur after the onset of seizure activity in a variety of animal models (Goldenring et al, 1986;Murray et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Protein levels and activity of CaMKII were observed to be re-distributed between cytosolic and membrane fractions in hippocampal tissues, and also showed overall decreases following global ischemic injury (Aronowski et al, 1992;Kolb et al, 1995;Shackelford et al, 1995). Studies also showed that time-dependent loss of synaptic responses was more intense in CA1 pyramidal cells than granule cells in hypoxia-induced hippocampal slices, and these changes were positively correlated with the levels of CaMKII activity (Westgate et al, 1994). Investigations using CaMKII subunit-deficient mouse further showed that brain tissues with loss of CaMKII activity become more susceptible to the infarction following ischemia (Murray et al, 1995).…”
Section: Introductionmentioning
confidence: 95%
“…To induce ischemic stress, slices were incubated in a modified ACSF containing 10 mM sucrose (to replace glucose) previously saturated with 95% N 2 /5% CO 2 based on the established hippocampal slice model of ischemia (38). At timed intervals samples (4 -8 slices) were removed from the medium and immediately homogenized in 400 l of Buffer A plus 10 mM iodoacetamide.…”
Section: Preparation Of Mouse Hippocampal Slices and Induction Ofmentioning
confidence: 99%